TOURIST AREA LIFE CYCLE STAGE AND THE IMPACT OF A CRISIS - BOJANIC, DAVID (ASEAN Journal on Hospitality and Tourism, 2005)
This paper examines the relationship between the tourist area life cycle and the recovery period following a crisis. There have been many studies of the tourist area life cycle theory and its application to the evolution of a tourism destination or resort. While it is clear that a tourism destination follows an asymptotic curve from its inception through development and stagnation, it is not clear how destinations in various stages of the tourist area life cycle are impacted by a crisis. This study focuses on two countries in Southeast Asia (Singapore and Vietnam) that are indifferent stages of the life cycle. The purpose of the study is to examine the relative impact of the SARS epidemic on the visitor arrivals of the two nations. Both ASEAN nations were exposed to the crisis, and the results show that the impact of the crisis, and the resulting recovery, did vary according to the life cycle stage.